2021
DOI: 10.1093/g3journal/jkab175
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative interactions: the disease outcome of Botrytis cinerea across the plant kingdom

Abstract: Botrytis cinerea is a fungal pathogen that causes necrotic disease on more than a thousand known hosts widely spread across the plant kingdom. How B. cinerea interacts with such extensive host diversity remains largely unknown. To address this question, we generated an infectivity matrix of 98 strains of B. cinerea on 90 genotypes representing eight host plants. This experimental infectivity matrix revealed that the disease outcome is largely explained by variations in either the host resistance or pathogen vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 87 publications
1
40
0
Order By: Relevance
“…Although the S. sclerotiniorum isolate used here was initially obtained from field grown lettuce, our analysis was restricted to single isolates of both pathogens. Previous studies using B. cinerea have indicated that there is a high level of isolate-specificity to quantitative resistance loci (Zhang et al 2016 ) and data on disease outcome using 98 B. cinerea isolates and 90 genotypes of eight plant hosts (including lettuce) demonstrated a much greater impact on lesion size from the B. cinerea isolate (40–71%) than the host genotype (3–8%) (Caseys et al 2021 ). Similarly, in B. napus both pathotype-specific and pathotype-independent resistance against S. sclerotiorum has been identified (Neik et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the S. sclerotiniorum isolate used here was initially obtained from field grown lettuce, our analysis was restricted to single isolates of both pathogens. Previous studies using B. cinerea have indicated that there is a high level of isolate-specificity to quantitative resistance loci (Zhang et al 2016 ) and data on disease outcome using 98 B. cinerea isolates and 90 genotypes of eight plant hosts (including lettuce) demonstrated a much greater impact on lesion size from the B. cinerea isolate (40–71%) than the host genotype (3–8%) (Caseys et al 2021 ). Similarly, in B. napus both pathotype-specific and pathotype-independent resistance against S. sclerotiorum has been identified (Neik et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…SNP-based GWAS based on a single reference genome dataset have been successful in describing the genetic basis of complex pathogen traits (Mohd-Assaad et al 2016; Pereira et al 2020b; Caseys et al 2021; Singh et al 2021). By expanding the number of reference genome SNP datasets used for GWAS, we identified substantially more independent loci than what was previously identified using the same phenotype dataset (Dutta et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although the S. sclerotinia isolate used here was initially obtained from field grown lettuce, our analysis was restricted to single isolates of both pathogens. Previous studies using B. cinerea have indicated that there is a high level of isolate-specificity to quantitative resistance loci (Zhang et al 2016) and data on disease outcome using 98 B. cinerea isolates and 90 genotypes of eight plant hosts (including lettuce) demonstrated a much greater impact on lesion size from the B. cinerea isolate (40-71%) than the host genotype (3-8%)(Caseys et al 2021). Similarly, in B. napus both pathotype-specific and pathotype-independent resistance against S. sclerotiorum has been identified (Neik et al 2017).…”
Section: Discussionmentioning
confidence: 99%